Effects of xylanase on yellow-feather broiler diets - AI, QIN; ZHAO, JIANGTAO; TAN, HUIZE; ZHANG, CHUNLEI; XU, JINGREN; FENG, DINGYUAN; ZUO, JIANGJUN (The Indian Journal of Animal Sciences, 2018)
To evaluate the effect of xylanase on broiler diets, we carried out two trials. In experiment 1, broilers were randomly assigned to six wheat-maize-soybean meal diet groups with different xylanase concentrations (0–500 mg/kg-1). In experiment 2, broilers were randomly assigned to several experimental groups consisting of two metabolic methods (total tract excreta collection and ileal digesta collection) and two xylanase concentrations (0 and 244.23mg/kg-1). Based on the results, xylanase supplementation significantly increased the digestibility of dry matter, gross energy and apparent metabolizable energy. These corresponding values were maximized at 300 mg/ kg-1 xylanase. The coefficients of variation (CVs) for DM, GE and AME in the ileal digesta collection method were about 10%, whereas those in the total tract collection method were only about 1.7%. Regression analysis showed that a segmented model satisfactorily described the dose-response relationship. Compared to the ileal digesta collection method, the total tract excreta collection method was more efficient for evaluating the effects of xylanase. These results provide valuable information on the optimal nutrition of broilers.